The characterization of mechanical behaviour on kenaf fibre / polypropylene composites - Mat Husin, Muhammad Muslimin (2017)
Global demand for wood plastic composite (WPC) has increased due to the increase of population and latest applications primarily in Malaysia industry today such as decking, chair and ceiling. However, the current WPC is worth investigating since such materials can be explored by enhancing their strength and quality through the treatment method. The objective of this study is to identify the effect of alkaline treatment on kenaf fibre in WPC system, to investigate the highest strength of kenaf fibre loading on mechanical properties in WPC, and to evaluate the morphology characteristics from fracture specimens related to the mechanical testing via scanning electron microscopy (SEM). Specimen was fabricated via injection moulding and hydraulic hot press using kenaf fibre (KF) as filler and polypropylene (PP) as the matrix. A tensile test was carried out to determine the tensile stress of the material. The result revealed treated specimen possesses high tensile stress at 5 wt.% sodium hydroxide (NaOH) compared to 10 wt.% and 20 wt.%. The optimum tensile stress was at 40 wt.% KF (5 wt.% NaOH, 5 wt.% MAPP) with the value 21.38 MPa. Flexural test was carried out on untreated and treated KF which is pure PP, 10 wt.% KF, and 20 wt.% KF by weight to PP. The result of flexural stress showed treated specimen lead better flexural at 20 wt.% PP/KF (5 wt.% NaOH) with 30.25 MPa. Meanwhile 40 wt.% KF (5 wt.% MAPP) give high fatigue life cycles at all stress level 90 %, 80 %, 70 %, 60 % and 50 % as the specimen structure less damage was induced during fatigue test. SEM is used to observe the morphological characteristics of PP/KF. The good interfacial bonding between KF and PP is 5 wt.% NaOH due of less impurities and lignin content. Overall 5 wt. % NaOH with 40 wt.% PP/KF (5 wt.% MAPP) showed the best result and it is worth to replace the current kenaf fibre polymer composites product.